Early musical training benefits to non-musical cognitive ability associated with the Gestalt principles - Hou, Jiancheng; Chen, Chuansheng; Dong, Qi (Frontiers in Psychology, 2023)
Musical training has been evidenced to facilitate music perception, which refers to the consistencies, boundaries and segmentations in music pieces that are associated with the Gestalt principles. The current study aimed to test whether musical training was beneficial to the nonmusic cognitive ability with Gestalt principles. Three groups of Chinese participants (with early, late, and no musical training) were compared in terms of their performances on the Motor-Free Visual Perception Test (MVPT). Results showed that the participants with early musical training had significantly better performance on the Gestalt-like Visual Closure subtest, but no significance on other Gestalt-unlike subtests (Visual Memory, Visual Discrimination, Spatial Relationship, Figure Ground in MVPT), than those with late and no musical training. This study suggests the benefit of early musical training on the non-music cognitive ability with Gestalt principles.